In silico primer design and CpG island detection in HSP90 gene chicken (Gallus gallus) - Nisa Sholihatul Ummah; Any Aryani; Hertien Koosbandiah Surtikanti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.